Flowering variation induces apple maturity variation at harvest - Tang, Haidee; Zhai, Xiaojun; Xu, Xiangming (Frontiers in Agronomy, 2025)
Most studies treat flowering time of all fruit within an apple orchard as a single date, overlooking the variability in flowering time both between trees and among individual flowers on the same tree. Consequently, the simplified approach of using a single flowering date may contribute to inaccuracies in harvest time predictions in previous models, impacting fruit quality. In our study, we aim to analyze the variance caused by flowering time on apple maturity by calculating the number of growing hours using the linear Growing Degree Hour (GDH), non-linear GDH and Thermodynamic models and correlating them to maturity. We also determine the variance caused by year, canopy region and tree-to-tree variability. We found that the effect due to the variability in flowering time is cultivar dependent, with Cox’s Orange Pippin having the largest effect (18.4 - 18.7%), followed by Gala (13.42 - 14.71%), Golden Delicious (5.86 - 6.15%), Braeburn (2.88 - 3.37%) and almost no effect on Fuji (0.52 - 0.61%). Seasonal and tree differences had a smaller impact on fruit maturity, while canopy region showed no significant effects.